Is it a journey worth taking? Experiences of second career academics transitioning into higher education - Dunn, S.; Tshozi, M.; Baron, J; Nendauni, L. (South African Journal of Higher Education, 2025)
The evolving landscape of higher education has witnessed an increasing number of individuals from various professional backgrounds transitioning into academia as second-career academics. This article explores the experiences of such academics, focusing on the motivations, challenges, and rewards associated with this significant career change. Employing a collaborative autoethnography approach, four academics from diverse disciplines and universities in the Western Cape province of South Africa shared their personal narratives. The analysis revealed motivations such as a perceived calling to academia and a desire for career growth. However, they faced challenges such as adapting to new teaching methodologies, managing diverse classrooms, and a lack of institutional support and mentorship. Balancing academic responsibilities with previous professional identities and handling academic administrative tasks were also significant hurdles. Despite these obstacles, the participants experienced substantial professional development and personal fulfilment. These findings accentuate the critical importance of providing structured support systems, comprehensive induction programmes, and ongoing professional development opportunities to facilitate smoother transitions for second-career academics. In entirety, the cultivation of a reflective academic community, coupled with robust mentorship programmes, can significantly enhance the integration and retention of second career academics within academia.